МODELLING OF FUTURE UKRAINE’S HIGH-SPEED RAILWAYS WITH SHARED USE FOR PASSENGERS AND CARGO SERVICE - Pozdniakov , Andrii (Science-based technologies, 2024)
The possibilities of joint utilization of future high-speed railways in Ukraine's transportation system, both for passenger and specific freight categories, are examined. A methodology for justifying the rational ratio of passenger and freight trains on the lines is proposed, along with the determination of technological and economic parameters for the operation of high-speed railways within Ukraine's multimodal transportation system. An economic-mathematical model is described, which allows for the optimization of design and technological decisions during the construction and operation of high-speed railways, depending on the economic and other conditions of their operation.